Effect of a professional soccer match in skin temperature of the lower limbs: a case study - de Andrade Fernandes, A.; Mendonça Pimenta, E.; Gomes Moreira, D.; Sillero-Quintana, M.; Bouzas Marins, J. C.; Figueiredo Morandi, R.; Kanope, T.; Silami Garcia, E. (Journal of Exercise Rehabilitation, 2017)
The purpose of this study is to analyze the relationship between lower limbs skin temperature (Tsk) recorded by infrared thermography and creatine kinase (CK) response following an official soccer game. A professional soccer player, from the first division Brazilian League, defender, 27 years and 183 cm of height was analyzed. Measures of Tsk with a thermal camera and blood CK concentrations were obtained 24 hr before (24H-PRE), 24 (24H-POST) and 48 hr (48H-POST) after an official match. The results showed that CK values were 193 U/L 24 hr before, rising to 1,083 U/L 24 hr after the game and 414 U/L 48 hr after the game. Anterior thigh Tsk was 31.5°C, 33.8°C, and 31.8°C in the moments 24H-PRE, 24H-POST, and 48H-POST, respectively. Similarly, anterior leg presented temperature of 31.2°C, 33.3°C, and 31.5°C at the same moments. Qualitative analysis of the thermograms showed that whole lower limbs are much warmer 24 hr after the match and certain areas as the right anterior thigh, the left anterior leg, both anterior ankles, and both posterior thighs have not fully recovered their initial Tsk 48 hr after the match. The results of this study indicate that participation in a professional soccer match can lead to significant increases in Tsk values measured by IRT 24 hr after the match. Considering this variable as an indicator of muscular damage, it could help in the process of training control, being part of an injury prevention program in professional soccer clubs.